Natural Polymorphisms in Arabidopsis Result in Wide Variation or Loss of the Amylose Component of Starch. Issue 2 (6th November 2019) - Seung, David; Echevarría-Poza, Alberto; Steuernagel, Burkhard; Smith, Alison M.
Abstract : Arabidopsis accessions carrying polymorphisms in the GRANULE BOUND STARCH SYNTHASE gene vary widely in the amylose content of leaf starch, and some produce amylose-free starch. Abstract: Starch granules contain two Glc polymers, amylopectin and amylose. Amylose makes up approximately 10% to 30% (w/w) of all natural starches thus far examined, but mutants of crop and model plants that produce amylose-free starch are generally indistinguishable from their wild-type counterparts with respect to growth, starch content, and granule morphology. Since the function and adaptive significance of amylose are unknown, we asked whether there is natural genetic variation in amylose synthesis within a wild, uncultivated species. We examined polymorphisms among the 1, 135 sequenced accessions of Arabidopsis ( Arabidopsis thaliana ) in GRANULE-BOUND STARCH SYNTHASE ( GBSS ), encoding the enzyme responsible for amylose synthesis. We identified 18 accessions that are predicted to have polymorphisms in GBSS that affect protein function, and five of these accessions produced starch with no or extremely low amylose (< 0.5% [w/w]). Eight further accessions had amylose contents that were significantly lower or higher than that of Col-0 (9% [w/w]), ranging from 5% to 12% (w/w). We examined the effect of the polymorphisms on GBSS function and uncovered three mechanisms by which GBSS sequence variation led to different amylose contents: (1) altered GBSS abundance, (2) altered GBSS activity, and (3) altered affinity of GBSS for binding PROTEIN TARGETING TO STARCH1—a protein that targets GBSS to starch granules. These findings demonstrate that amylose in leaves is not essential for the viability of some naturally occurring Arabidopsis genotypes, at least over short timescales and under some environmental conditions and open an opportunity to explore the adaptive significance of amylose.